SCREEN TIME AND AGGRESSION IN ADOLESCENTS: A MODERATING ROLE OF CONTENT-BASED MEDIA EXPOSURE - Majeed, Saima (Journal of Pakistan Psychiatric Society, 2023)
Objectives: This study was designed to explore the relationship between excessive screen time, content-based media exposure, and aggression in adolescents. Another important aim was to examine the moderating role of content-based media exposure between screen time and aggression.Study Design: A correlational cross-sectional research design was followed.Place and Duration of Study: Forman Christian College (A chartered University). March 2022-July 2022). Subjects and Methods:  A convenient sample of 250 adolescents with an age range of 13 to 17 years was drawn from two public and two private schools and colleges in Lahore. The measures for data collection were the Screen-Time Addiction Questionnaire Content-Based Media Exposure Scale and The Aggression Scale are used to understand the strategic elements of how screen time shapes the world around adolescents that may lead to aggressive behaviors.Results: The results of the Pearson product-moment correlation indicated that screen time has a positive relationship with both anti-social (.32* p<.05) and neutral content (.37* p<.05) of media exposure. Similarly, anti-social media exposure has a significant positive relationship (56** p<.01) with aggression. Violent and neutral content exposure has an inverse relationship (-.40** p<.01) with each other. Anti-social media exposure proved a significant positive (β=4.32, p<.05) predictor of aggression. Furthermore, media exposure significantly moderates the relationship 1.98*** p<.001).Conclusion: Mean scores indicated that the present population spent more time on screens watching violent, anti-social content and scored high on aggression. Adolescents who spent more time watching anti-social /violent content scored high on aggression.  Educators, parents, and content designers should keep this thing in mind for designing online content for the public, especially for children and adolescents.